Injury incidence rate according to mechanism, body location, and type in basketball players: a systematic review and meta-analysis - Stojanovic, E.; Scanlan, A. T.; Radovanovic, D.; Jakovljevic, V.; Živkovic, V.; Faude, O.; Fox, J.; Raasch, K.; Ferrauti, A. (Sports Medicine, 2025)
Background: Despite the strong research attention dedicated to reporting the injury incidence rate (IR) in many samples of basketball players, a dedicated review regarding the epidemiology of the injuries encountered in the sport is needed. Objective: We aimed to meta-analyze the literature to quantify the IR of injuries according to mechanism, body location, and type while considering player sex, playing level, and exposure settings in basketball players. Methods: PubMed, MEDLINE, and Google Scholar were searched from inception to October 2024. Studies reporting the injury IR in basketball players calculated using the number of athletes exposures (AEs) and/or exposure hours were eligible for inclusion. Results: Following screening, 22 studies (15 reporting mechanism data, 21 reporting body location data, and 17 reporting type data) were included in the systematic review and meta-analysis. Player contact (42.9%) and non-contact (25.0%) were the most common injury mechanisms, with IRs of 0.156 and 0.093 per 100 AEs. Ankle injuries (25.8%, IR = 0.075 per 100 AEs) and knee injuries (15.5%, IR = 0.046 per 100 AEs) accounted for 41.3% of reported injuries. The most common injury types were ligament sprains (IR = 0.102 per 100 AEs) followed by muscle/tendon strains (IR = 0.037 per 100 AEs) and concussions (IR = 0.028 per 100 AEs). A concerning finding was the proportion of head and facial injuries (16.3%), particularly among female players. Female players displayed significantly higher IR of ball contact injuries, knee injuries, dislocations/subluxations, and concussions compared with male players. Injury IR was consistently higher in games than practice settings, as well as in collegiate compared with high-school players. Conclusions: This study provides comprehensive and contemporary analyses of one of the most investigated areas in the basketball literature, injury IR. The provided results may inform the development of preventive measures to mitigate injury risk considering the notable factors identified.